Language Use and Identity of Foochow Chinese in Malaysia - Ting, Su Hie; Ting, Su Lin (LCS, 2020)
The study examined the language use and identity of Foochow respondents in Sarawak, Malaysia. Analysis of questionnaire data from 376 respondents (188 parents, 188 children) showed that more parents could speak Foochow whereas more children could speak Mandarin. The younger Foochow haslower self-reported Foochowproficiencythan their parents. They use Foochow in fewer domains (family, friendship, religious, transactions)compared to their parents who speakFoochow in all do-mainsof language use. There are significant differences between the strength of Foochow identity for parents and children. The strength of Chinese ethnic identity for parents and children are also signifi-cantly different. The Foochow identity is positively associated with Foochow usage and negatively as-sociated with Mandarin usage, but no inverse relationship was found between Foochow identity and Chinese identity. The younger Foochow ismore detached from their Foochow identity, and this gen-erational change is engendered by the rise of Mandarin.